2003
DOI: 10.1016/s1053-8119(03)00351-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of error correction in sensorimotor-synchronization

Abstract: In a sensorimotor synchronization task requiring subjects to tap in synchrony with an auditory stimulus, occasional perturbations (i.e., interval changes) in an otherwise isochronous sequence of auditory metronome stimuli are known to be compensated remarkably swift and with surprising precision, even when they are too small to be consciously perceived. To investigate the neural substrate and the informational basis of error correction in sensorimotor synchronization, we recorded movement-related, auditory-evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
76
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 62 publications
15
76
2
Order By: Relevance
“…For example, Repp (2002) showed that error correction performance for positive shifts was more variable than that of negative shifts. Furthermore, we have shown an over-correction for positive shifts as in previous studies (Praamstra et al, 2003;Thaut et al, 1998), whose degree was significantly less after practicing. By contrast, error correction of negative shifts was stable both during the testing sessions within a day, and during the testing sessions over a few days apart (Bijsterbosch et al, 2011a).…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…For example, Repp (2002) showed that error correction performance for positive shifts was more variable than that of negative shifts. Furthermore, we have shown an over-correction for positive shifts as in previous studies (Praamstra et al, 2003;Thaut et al, 1998), whose degree was significantly less after practicing. By contrast, error correction of negative shifts was stable both during the testing sessions within a day, and during the testing sessions over a few days apart (Bijsterbosch et al, 2011a).…”
Section: Introductionsupporting
confidence: 79%
“…The tones were presented with an IOI of 600 ms based on the finding that an anticipatory response (i.e., negative mean asynchrony) could be obtained within the IOI range from 450 to 1,500 ms (Miyake et al, 2004). While an IOI of 500 ms was utilized in Praamstra et al (2003), we extended it to 600 ms to allow more time for CNV generation as 500 ms might not be enough for detailed CNV analyses (see Figure 7, Praamstra et al, 2003). The tone sequence contained occasional phase shifts.…”
Section: Stimuli and Tasksmentioning
confidence: 99%
See 3 more Smart Citations